Perencanaan Manajemen Konstruksi Pada Pembangunan Gedung Kantor Pelayanan Pajak Jalan Arteri Supadio Kabupaten Kubu Raya - Djamirul Akmal, Ijlal; Riansyah, Reza; Utomo, satriyo; widhiyastuti, Rahayu (Jurusan Teknik Sipil Polnep, 2023)
One of the reasons for the construction of the Kubu Raya Regency Tax Service Office building is because currentlyit still does not have a tax service office, the increasing population, the payment of taxes in Kubu Raya reallyneeds a tax service building, which currently has not been made by the local government. Therefore, structuralplanning and plan drawings are carried out. The planning for the building of the Tax Service Office Building isplanned for Jalan Arteri Supadio, Kubu Raya Regency. Therefore, to realize the building of the Tax Service OfficeBuilding, proper construction management is needed, so that this building can be realized. In the construction ofthe Tax Service Office Building, construction management is planned with methods in the form of a costmanagement system, time management, human resource management (HR), quality management, and safety,health, work (K3) management. Based on the results of the analysis above, the total cost of structural workobtained a value of Rp. 13,378,930,910.29. The time required for the completion of the structural work is 180calendar days. For quality planning in the form of quality control and specification tables. For human resourcemanagement in the form of a project organizational structure. And control of potential OHS hazards for each jobsuch as Personal Protective Equipment (PPE). The highest number of PPE are safety helmets, safety shoes, safetygloves, masks and marker vests. each with a total of 278.